An update on predicting renal progression in IgA nephropathy. Issue 3 (May 2018) - Barbour, Sean; Reich, Heather
Abstract : Purpose of review: Immunoglobulin A (IgA) nephropathy (IgAN) is a heterogeneous disease, and predicting individual patient risk of renal progression is challenging. Recent studies provide new evidence regarding the use of clinical, histologic, and biomarker predictors of renal outcome in IgAN. Recent findings: A meta-analysis of clinical trials demonstrated that early change in proteinuria is a valid surrogate outcome measure for longer term decline in renal function, which supports the use of proteinuria to dynamically re-evaluate patient prognosis over time. The MEST histologic classification has been further validated in a large European cohort. An international multiethnic observational study demonstrated that crescents are independently associated with renal outcome, and as a result a crescent score (<25% versus >25% of glomeruli) has been added to MEST. Proteinuria, estimated glomerular filtration rate (GFR), and blood pressure at the time of biopsy can be used to accurately predict prognosis when combined with MEST, instead of using 2 years of follow-up data. Currently, no available risk prediction model that combines clinical and histologic predictors has been sufficiently validated for routine use. There are multiple biomarkers that have been studied in IgAN, however none have been externally validated and shown to improve prediction beyond clinical and histologic risk factors. Summary: Proteinuria, estimated GFR, blood pressure, and the MEST-C score are the most readily available risk factors to predict renal prognosis in IgAN. Future research is required to develop and validate methods of integrating these risk factors together to accurately risk stratify individual patients, and provide the framework for evaluating biomarkers capable of further improving risk prediction.